Answer:
its 45
Step-by-step explanation:
Answer:
Step-by-step explanation:
(-2x-3)(4x+5) = -(2x+3)(4x+5) = -(8x^2+12x+10x+15) = -8x^2 - 22x - 15
Leading coefficient is -8
Answer:
1)
2)
Step-by-step explanation:
Assuming that our function is for the first case and for the second case.
Part 1
We can rewrite the expression like this:
And we can reorder the terms like this:
Now if we apply integral in both sides we got:
And after do the integrals we got:
Now we can use the initial condition
And the final solution would be:
Part 2
We can rewrite the expression like this:
And we can reorder the terms like this:
Now if we apply integral in both sides we got:
And after do the integrals we got:
Now we can use the initial condition
And the final solution would be:
Answer:
w ≥ 6
Step-by-step explanation:
51 ≤ 15 +6w
51-15 ≤ 6w
36 ≤ 6w
6w ≥ 36
w ≥ 36/6
w ≥ 6